POLARIZED NEUTRON REFLECTION AS A PROBE OF INPLANE MAGNETIZATION VECTOR ROTATION IN MAGNETIC MULTILAYERS - Blundell, S; Bland, J (1993)
We demonstrate that polarised neutron reflection (PNR) sensitively probes the in-plane layer-dependent magnetisation vector profile in multilayer structures on nanometre lengthscales. We derive the spin-dependent reflectivity using an optical method for a general multilayer, and discuss two regimes: first, the kinematical diffraction limit; second, just above critical reflection, where multiple reflections and refraction dominate. © 1993.